2007
DOI: 10.1007/s00417-007-0703-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial adhesion to conventional hydrogel and new silicone-hydrogel contact lens materials

Abstract: Conventional hydrogel contact lenses exhibit significantly lower bacterial adhesion in vitro than silicone-hydrogel ones. This could be due to the greater hydrophobicity but also to the higher oxygen transmissibility of silicone-hydrogel lenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 28 publications
(39 reference statements)
4
44
1
Order By: Relevance
“…Although this is consistent with other studies for other bacterial strains (Borazjani et al, 2004;Santos et al, 2008), it challenges the established relationship between microbial adhesion and lens surface hydrophobicity (Pritchard et al, 1999;Doyle, 2000;Young et al, 2002;van Oss, 2003;Giraldez et al, 2010b). This discrepancy could be explained by the different extents of microbial colonization observed for different bacterial strains, and/or the different methodologies employed (Henriques et al, 2005;Kodjikian et al, 2007). In fact, most P. aeruginosa strains have a more hydrophilic surface than S. epidermidis or other bacteria (Gottenbos et al, 2001;MitikDineva et al, 2009).…”
Section: Staphylococcus Epidermidissupporting
confidence: 87%
See 1 more Smart Citation
“…Although this is consistent with other studies for other bacterial strains (Borazjani et al, 2004;Santos et al, 2008), it challenges the established relationship between microbial adhesion and lens surface hydrophobicity (Pritchard et al, 1999;Doyle, 2000;Young et al, 2002;van Oss, 2003;Giraldez et al, 2010b). This discrepancy could be explained by the different extents of microbial colonization observed for different bacterial strains, and/or the different methodologies employed (Henriques et al, 2005;Kodjikian et al, 2007). In fact, most P. aeruginosa strains have a more hydrophilic surface than S. epidermidis or other bacteria (Gottenbos et al, 2001;MitikDineva et al, 2009).…”
Section: Staphylococcus Epidermidissupporting
confidence: 87%
“…Notwithstanding, Santos et al were unable to detect any difference in microbial adhesion when comparing unworn silicone hydrogel and conventional hydrogel CL. This discrepancy could be explained by the different extents of microbial colonization observed for different S. epidermidis strains, and/or the different methodologies employed (Henriques et al, 2005;Kodjikian et al, 2007). In both hydrophobic and hydrophilic groups, the lenses showing the lowest Ra values (omafilcon A and comfilcon A) also returned the lowest numbers of S. epidermidis CFU, despite their high Rku and Rsk values.…”
Section: Staphylococcus Epidermidismentioning
confidence: 99%
“…47,48 After different aging durations, implants were incubated with a human isolate of S. epidermidis to imitate the natural contamination of silicone specimens for our in vitro study, a method that has proven to be valuable before. 26,49,50 Surprisingly, the findings of this study suggest that artificial aging does not affect R a and SFE of silicone specimens. The lack of change of surface characteristics due to artificial aging is rather striking as, for example, very resistant and hard-wearing dental materials have shown evident changes after the process of artificial aging.…”
Section: Discussioncontrasting
confidence: 61%
“…This is also similar to the adhesion of these bacterial types to contact lenses. 21,22 The study has shown that the level of lens case contamination is determined by several factors such as the cleaning regimen, the potency of disinfecting solutions used to rinse lens case wells, and the internal lens well design (which affects the adhesion and ease of detachment of bacteria). It is recommended by lens care practitioners and manufacturers that lens wearers use a disinfecting solution with its accompanying lens case (i.e., from the same manufacturer).…”
Section: Discussionmentioning
confidence: 99%